De la simultanéité en histoire globale - Adrien Delmas (L'Atelier du CRH)
This essay focuses on simultaneity as a discursive figure of global history. The question is rather simple: why does global history sometimes use simultaneities to demonstrate connections? Taking some examples from recent historiography (Sanjay Subrahmanyam, Serge Gruzinski, Romain Bertrand), we would like to show that the question of simultaneity in its relation to large-scale history is nothing new. Without pretending to be exhaustive, we will dwell on a few cases (Polybius, Eusebius of Caesarea, João de Barros, Joseph Scaliger) that demonstrate how simultaneity is one of the oldest concerns of the desire to embrace the whole known world at a given moment, and to propose a narrative of it. Finally, we will return to the question of present-day historiography to ask whether simultaneity requires us to switch from a science of the conditions of possibility (Michel Foucault) to a science of the conditions of availability